Evaluating antibiotics for use in medicine using a poloxamer biofilm model - Cochrane Christine A; Clutterbuck Abi L; Dolman Jayne; Percival Steven L (BMC, 2007)
Abstract Background Wound infections, due to biofilms, are a constant problem because of their recalcitrant nature towards antibiotics. Appropriate antibiotic selection for the treatment of these biofilm infections is important. The traditional in vitro disc diffusion method for antibiotic selection uses bacterial cultures grown on agar plates. However, the form of bacterial growth on agar is not representative of how bacteria grow in wounds and other tissue sites as here bacteria grow naturally in a biofilm. The aim of this research was to test a more appropriate method for testing antimicrobial efficacy on biofilms and compare with the standard methods used for antibiotic sensitivity testing. Methods Outer Membrane Protein analysis was performed on E.coli, Staphylococcus aureus, Pseudomonas aeruginosa, Proteus mirabilis and Acinetobacter juni when grown on Mueller Hinton agar ('quasi-biofilm state') and 30% Poloxamer hydrogel ('true- biofilm state). Susceptibility to antibiotics on 28 clinical isolates was determined using the modified Kirby Bauer disc diffusion method, on agar and 30% Poloxamer. Results Similar outer membrane proteins [OMPs] were identified in bacteria grown in a biofilm state and on a 30% poloxamer hydrogel, which were very different to the OMPs identified in bacteria grown on Mueller-Hinton agar and broth. There was a significant difference between the means of the clearance zones around the antibiotic discs on standard agar and poloxamer gels [P < 0.05]. The zones of clearance were generally smaller for poloxamer-grown bacteria than those grown on standard agar. Diffusion distances of various antibiotics through agar and 30% poloxamer showed no significant difference [P > 0.05]. Conclusion The findings of this experiment suggest that poloxamer gel could be used as an appropriate medium on which to conduct biofilm antibiotic susceptibility tests as it enables bacteria to be grown in a state representative of the infected surface from which the culture was taken.